Penanda DNA mikrosatelit Kromosom-Y untuk Penelusuran Soroh-soroh/Kawitan Masyarakat Bali - I Ketut Junitha (Journal of Tropical Ethnobiology, 2021)
Soroh is a Balinese term for a clan in Indonesian. Each soroh is a group of Balinese Hindus who believe they are descended from one common ancestor, and has one main temple as a place of worship to the ancestors, which is called the kawitan temple. Each main soroh can be divided into several sub-soroh based on the male lineage of the main ancestor. Each sub-soroh also has a temple for their ancestors’ worship which is also called pura kawitan. Therefore, there are known subsoroh and pura kawitan main temples, whose members are a combination of sub-soroh and sub-sections. Soroh Catur Sanak Bali Mula believes he is a descendant of Mpu Kamereka which developed into four sub-soroh, namely Kayu Selem, Celagi, Kayuan, and Terunyan. The family system in Bali adheres to a patrilineal descent where all children from one family will follow the cheer of their father. For Balinese Hindus, knowing their soroh or kawitan temple is an obligation to be able to offer prayers to their kawitan temple as a form of respect for each offspring to their ancestors. Losing traces of ancestors (kawitan) is believed to be a major problem in the family life. Based on the belief that each soroh is descended from one ancestor and the family system in Bali adheres to a patrilineal lineage, soroh or kawitan tracing can be carried out by DNA analysis with Ychromosome microsatellite markers. DNA or genes on the Y chromosome that are only present in males will be passed from males to only males and so on. Therefore, the Y-chromosome microsatellite profile can be used as a search tool for Soroh or Kawitan in Balinese society.